Georges Bataille and Roger Caillois at the College of Sociology (1937-1939): genealogy of a philosophical dialogue (and of a Rupture) - Petel-Rochette, Nicolás (Estudios de Filosofía, 2021)
What do the works that were discussed during the sessions of the “College of Sociology” tell us today? By examining the respective influences of Roger Caillois and Georges Bataille, this article aims to show that the dialogue that brought them together, and that would eventually separate them, is rooted in nineteenth-century philosophical debates. Considering a broader theoretical horizon as a framework for the College of Sociology, this article also aims to offer a reading of why such eclectic interests crossed paths during its sessions. This analysis is carried out following the question that, in our opinion, motivated the Caillois/Bataille debate: what institution could subvert the principle of the teleological progress of modernity? In short, through the study of the Caillois/Bataille discussions and disagreements, this article aims to underline some limits that led to the dissolution of the College of Sociology.